The microstructural and mechanical properties of glass fiber reinforced geopolymer composites - Yaakob, S.M. (Microscopy Society of Malaysia, 2019)
Geopolymers are inorganic aluminosilicate materials that possess excellent mechanical properties and good thermal resistance properties. However, the limitation with brittle behaviour and shrinkage effect is there. One of the best solutions to address the limitation is by incorporation of fibers to a brittle matrix as to improve the compressive and flexural strength of geopolymers. This study broadly evaluates the effects of glass fiber content at 0.2 to 2.0wt with length of 6mm and 12mm on microstructural and mechanical properties of geopolymer composites. The compression and flexural strength of composites was reported, as the morphological structure of fracture surface and fiber-matrix interface was examined using Scanning Electron Microscopy (SEM). Results show a porous surface and partially reacted fly ash were observed in the microstructural analysis of all geopolymers. The incorporation of glass fiber up to 1wt into the geopolymer matrix reduces the shrinkage and enhances the flexural and compressive strength of the composites. Microstructural images demonstrated the glass fibers act as filler for pores within geopolymer matrix, producing denser geopolymer composite, thus improving the mechanical properties. Further increase the fiber content up to 2wt, resulted lower level of compression and flexural strength due to shrinkage effect. Â© Malaysian Journal of Microscopy (2018). All rights reserved.